Diurnal Cortisol in Left-Behind Adolescents: Relations to Negative Family Expressiveness and Internalizing Problems - Li, Man; Lan, Qili; Qiu, Lirong; Yuan, Yidan; He, Fengjiao; Zhang, Chen; Zhang, Linlin (Frontiers in Public Health, 2022)
Despite the accumulating evidence for increased risks for behavioral problems in left-behind adolescents in China, little research has explored their HPA axis functioning, which is hypothesized to play a central role in the association between early adversity and health. In the present study, we designed a longitudinal study to examine HPA axis function in left-behind adolescents and its mediating role in the association between family emotional expressiveness and internalizing problems. Participants were 81 adolescents (44 female; 37 male) aged 11–16 years. Salivary cortisol samples were collected six times a day for two consecutive days on regular school days. Negative family expressiveness (NFE) and internalizing problems were measured using self-report questionnaires. The results showed that NFE was negatively associated with diurnal cortisol, and diurnal cortisol was negatively associated with internalizing problems. Further analysis showed that diurnal cortisol secretion measured by AUC (area under the curve) mediated the association between NFE and internalizing problems. Our findings extended the existing literature about left-behind children via a psychoneuroendocrinological perspective, documenting the negative consequences of the family environment for youth health and development.